Delivering data analytics for a software product - Šulc, Jan (2023)
This thesis focuses on taking over and building data analytics in a prop-tech startup company developing its own software product. The first part starts with an analysis of the current state of data analytics and getting to know the whole environment to use this knowledge further to assess the critical parts that need to be prioritized. The rest of the chapters describe specific areas of improvement, starting with delivery process improvements that set the foundation for all following work. Then I approach the current data acquisition process, which results in a significant data architecture change to further standardize and improve the current solution. Next, I describe significant improvements implemented in the analytical database, which concludes the database and data pipeline parts and leads into the last chapter, which focuses on the semantic and visualization layer.